MANAJEMEN PENDIDIKAN KEWIRAUSAHAAN DALAM MENUMBUHKAN JIWA KEMANDIRIAN SANTRI DI PONDOK MODERN DARUSSALAM GONTOR KAMPUS 7 - Arrahman, Hafizh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the management of entrepreneurship education in fostering the spirit of independence among students at Pondok Modern Darussalam Gontor Campus 7. The background of this research stems from the growing importance of entrepreneurship in Islamic educational institutions to enhance students’ economic self-sufficiency and leadership abilities. The research focuses on the planning, implementation, and evaluation of entrepreneurship education programs within the pesantren environment. This qualitative study employs a case study approach, using data collection techniques such as observation, in-depth interviews, and documentation, with purposive sampling applied to select participants including students, teachers, and pesantren administrators who are directly involved in the entrepreneurship program. Data analysis was conducted through thematic analysis. The findings reveal that the entrepreneurship education program at Gontor Campus 7 is integrated with Islamic values and is implemented through structured student-managed business units such as cooperatives, cafeterias, and laundry services. These activities provide real-life business experience that fosters independence, responsibility, and critical thinking. However, challenges were identified in terms of planning specificity, organizational clarity, and the effectiveness of motivation systems. The study concludes that a comprehensive and adaptive management model, which aligns with local needs and religious values, is essential to effectively cultivate entrepreneurial spirit and student independence. The results contribute to the development of effective management strategies for entrepreneurship education in religious boarding school contexts. Keywords: entrepreneurship education, pesantren, student independence